(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
This study delves into the multifaceted landscape of energy efficiency management with the objective of rationalizing the utilization of energy resources. The article considers a methodical approach to the study of the level of energy intensity of economic activity, covering levels of management, from the macro level to the level of an individual enterprise. In general, it is advisable to supplement the proposed approach with existing methods that extend the content to the results of energy efficiency research. Using the Life Cycle Assessment (LCA) method and other methodologies, we explore various dimensions of energy resource utilization and the scale of energy efficiency management across different stages of the lifecycle. Additionally, the study introduces levels of energy efficiency management developed by the authors, providing a structured framework for optimizing energy use. Through rigorous analysis, we evaluate the environmental impacts, energy consumption patterns, and efficiency levels associated with diverse energy management strategies. Our findings illuminate key areas for improvement and optimization in energy utilization practices, offering insight beneficial for policymakers, industry stakeholders, and environmental advocates alike. By leveraging the comprehensive framework of LCA alongside the developed levels of energy efficiency management, this research contributes to a nuanced understanding of energy efficiency management, thereby facilitating informed decision-making towards sustainable energy utilization pathways. Examining the example of building the life cycle of gas production and highlighting the main stages of its transformation from a raw resource to a finished product for consumption allows for the consideration of the entire chain of creation of the added value of this energy resource and enables control of the level of its influence on the results of the activities of economic units involved in this chain, as well as the consequences of their impact on the environment. This allows us to conclude that the approach discussed in the article can be used both for researching the energy efficiency of individual enterprises, as well as their associations, industries, and the economy in general.